Bilateral radicular dens in dente in mandibular premolars - Kanika Gupta Verma; Suman Basavaraju; Sahil Jindal; Suresh Sachdeva (Wolters Kluwer Medknow Publications, 2013)
Dens invaginatus (DI) is a rare developmental anomaly that results from an invagination of the enamel organ into the dental papilla during odontogenesis. The invagination ranges from a slight pitting (coronal type) to an anomaly occupying most of the crown and root (radicular type). Radicular DI is an unusual dental anomaly. Although a clinical examination may reveal a deep fissure or pit on tooth surface, but radiographic examination is the most realistic way to diagnose the invagination. The objective of this case presentation is to report a rare case of radicular dens invaginatus bilaterally in mandibular premolars.